Pendampingan Strategi Branding Produk dan Desain Digital Canva pada Usaha Mikro, Kecil, dan Menengah di Kabupaten Banyuwangi - Ahmad Faizal; Cici Wijayanti; Mursidah Mursidah; Achmad Hadi Mubarok (Ngarsa: Journal of Dedication Based on Local Wisdom, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting local economic development; however, they continue to face significant challenges in strengthening brand identity and utilizing digital design for effective marketing. These challenges are also faced by MSMEs in Ringintelu Village, Banyuwangi Regency, where many businesses lack distinctive brand identities and competitive product visuals. This community engagement program aimed to enhance the capacity of MSME actors to develop effective branding strategies and optimize the use of Canva as an accessible digital promotional tool. The program employed a Participatory Action Research (PAR) approach integrated with community development and learning community frameworks through problem identification, participatory planning, branding workshops, digital design training, intensive mentoring, and continuous evaluation. The findings demonstrated substantial improvements in participants' understanding of branding principles, their ability to independently produce digital promotional materials, and the professionalism and consistency of product visual designs. Furthermore, the establishment of an MSME learning community fostered sustainable capacity building, strengthened brand identity, improved marketing effectiveness, expanded market opportunities, and ultimately enhanced the competitiveness of village-based MSMEs while contributing to sustainable local economic development Keywords: Product Branding, Digital Design, MSMEs, Canva Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki peran strategis dalam pembangunan ekonomi lokal, tetapi masih menghadapi kendala dalam penguatan branding dan pemanfaatan desain digital sebagai media pemasaran. Kondisi tersebut juga dialami pelaku UMKM di Desa Ringintelu, Kabupaten Banyuwangi, yang umumnya belum memiliki identitas merek yang kuat serta tampilan visual produk yang menarik dan kompetitif. Pengabdian ini bertujuan untuk meningkatkan kapasitas pelaku UMKM dalam menyusun strategi branding serta mengoptimalkan penggunaan aplikasi Canva sebagai media promosi yang mudah diakses. Metode yang digunakan adalah Participatory Action Research (PAR) dengan pendekatan community development dan learning community melalui identifikasi masalah, perencanaan partisipatif, workshop branding, pelatihan desain digital, pendampingan intensif, serta evaluasi berkelanjutan. Hasil pengabdian menunjukkan peningkatan pemahaman peserta mengenai konsep branding, kemampuan membuat materi promosi digital secara mandiri, serta kualitas visual produk yang lebih profesional dan konsisten. Selain itu, terbentuknya komunitas belajar UMKM mendorong keberlanjutan peningkatan kapasitas, memperkuat identitas merek, meningkatkan efektivitas pemasaran, memperluas peluang pasar, dan pada akhirnya memperkuat daya saing UMKM desa serta mendukung pengembangan ekonomi lokal secara berkelanjutan. Kata kunci: Branding Produk, Desain Digital, UMKM, Canva